Professional Competence of Teachers of Ukrainian Language and Literature as Psychological and Pedagogical Problem - Chubaruk, Olena (Pedagogical Discourse, 2015)
The work offers materials on theoretical research of professional competence of teachers of Ukrainian language and literature in psychological and pedagogical literature. The study clarifies the matter of competence approach, which has the following structural components: objectives of education, content of education, peculiarities of educational process, integral educational results within the activity theory of learning. The content of the notion «professional competence» has been specified. The paper analyses internal and external structure of professional competence of teachers of Ukrainian language and literature on the basis of theoretical research. By the results of the conducted analysis of scientific literature, we came to the conclusion that typical priority ideas, principles, functions, components of the competence approach, professional competences, which are conceptual as for the forming integral theory of the competence approach, have been mentioned in the foreign and national normative documents, works on psychology and pedagogics.